1996
DOI: 10.1055/s-2007-972811
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Plasma Free Tryptophan and Large Neutral Amino Acids Do Not Affect Perceived Exertion and Prolactin During 90 min of Treadmill Exercise

Abstract: It has been hypothesized that fatigue and prolactin (PRL) changes during endurance exercise are influenced by serotonin synthesis, and in turn, release. Such a change is thought to occur through an increase in blood free tryptophan (TRP) and a concomitant decrease in those large neutral amino acids (LNAA) which compete with free TRP for entry into the brain. For further investigation, 10 healthy athletes were randomly subjected to three test units (TU), each consisting of a treadmill run for 90 min. The speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 7 publications
(11 reference statements)
4
21
1
3
Order By: Relevance
“…The present elevations in free TRP/BCAA are in line with previous data obtained in younger men in response to moderate-intensity exercise. That is, when compared with previous studies of at least ~60 min of moderate-intensity exercise, the magnitude of increase in free TRP (-M04%) or free TRP/BCAA (+102%) from baseline levels observed in our study with older men was higher than most results reported in younger individuals (3,24,34). Nevertheless, greater elevations were observed in a study involving a regimen designed to lower muscle glycogen before exercise (40).…”
Section: Discussioncontrasting
confidence: 69%
“…The present elevations in free TRP/BCAA are in line with previous data obtained in younger men in response to moderate-intensity exercise. That is, when compared with previous studies of at least ~60 min of moderate-intensity exercise, the magnitude of increase in free TRP (-M04%) or free TRP/BCAA (+102%) from baseline levels observed in our study with older men was higher than most results reported in younger individuals (3,24,34). Nevertheless, greater elevations were observed in a study involving a regimen designed to lower muscle glycogen before exercise (40).…”
Section: Discussioncontrasting
confidence: 69%
“…Other studies have also reported increases in PRL which peaked at EXH with treadmill running (Struder et al 1996), following 5 h of cycling in trained individuals (Struder et al 1999), in heat acclimated men during EHS when hypohydrated (Cheuvront et al 2004), and in moderately (Melin et al 1988) and highly fit (Radomski et al 1998;Watson et al 2005a) individuals during exercise in the heat. Although T c was reported by Melin et al (1988), regression analysis was used to estimate the linear relationship between plasma PRL and T c .…”
Section: Prolactin As a Peripheral Indicator Of Central Fatiguementioning
confidence: 81%
“…Previous studies have demonstrated that elevation in plasma [FFA] displaces Trp from binding to albumin and consequently increases the free-Trp:LNAA ratio into the plasma [17,18,30,31]. Since Trp and the other LNAAs share the L-system carrier for crossing the BBB, the elevation in plasma free-Trp:LNAA ratio may favour brain Trp uptake and potentially increase brain 5-HT synthesis [32], and hence central fatigue [15,33].…”
Section: Discussionmentioning
confidence: 99%